Carbon fiber supported Co/Co3O4-embedded N-doped carbon microparticles for efficient overall seawater splitting and oxygen reduction. (1st February 2023) - Chen, Yang; Zhao, Xiaojun; Zhang, Qiujuan; Miao, Xinjia; Chen, Yan; Yang, Weiting; Pan, Qinhe
Abstract: Due to low cost and abundance, direct seawater splitting to produce hydrogen is an encouraging strategy to alleviate the consumption of fossil energy, while also avoiding freshwater stress. However, when natural seawater is utilized as the electrolyte, the catalysts on the cathode and anode of water splitting should not only have high activity to promote energy efficiency, but also have good stability and durability to resist the corrosion of chloride ions. Herein, a hierarchical carbon-based catalyst for hydrogen and oxygen evolution, ZIF-67/CF-1, was prepared by annealing a composite of ZIF-67 and carbon fiber (CF). It exhibits good electrocatalytic activity and stability for overall splitting in natural seawater and neutral PBS solution. Impressively, when an electrolyzer consisting of ZIF-67/CF-1||ZIF-67/CF-1 is applied to overall seawater splitting, the current density of 10 mA/cm 2 is achieved with a drive voltage of 2.46 V, which is only 0.28 V higher than precious metal-based electrolyzer (Pt/C||IrO2 ). Meanwhile, ZIF-67/CF-1 shows outstanding catalytic ability for oxygen reduction ( E 1/2  = 0.84 V, Tafel slope = 66.9 mV/dec), also demonstrating its application potential in rechargeable batteries and fuel cells. Graphical abstract: A hierarchical carbon-based electrocatalyst (ZIF-67/CF-1) were developed for oxygen evolution on the anode and hydrogen evolution/oxygen reduction on the cathode. It owns good activity, stability and durability for hydrogen and oxygen evolution in natural seawater, and has been used as a bifunctional catalyst for overall seawater splitting in a two-electrode electrolyzer. Additionally, ZIF-67/CF-1 exhibits the high half-wave potential and small Tafel slope value for oxygen reduction in 0.1 M KOH. Image 1 Highlights: The hierarchical carbon-based catalysts for HER, OER and ORR were prepared. ZIF-67/CF-1 exhibits good electrocatalytic ability for overall seawater splitting. The current density of 10 mA/cm 2 is achieved with a cell voltage of only 2.46 V. The ORR catalytic performance of ZIF-67/CF-1 is comparable to that of Pt/C. N-doped hierarchical carbon is beneficial to the electrocatalytic performance.